Disclosure of corporate social responsibility in tourism industry, sri lanka - Weerasinghe, D.R.M.; Pathirana, G.P.T.D.; Rajapaksha, C.M.; Perera, R.A.K.R.; Kaneshwaren, S. (University of Jaffna, 2019)
Studies that concentrate on the trend of Corporate Social Responsibility (CSR) disclosure in the Sri Lankan context, particularly in the hotel industry, are hardly found. The present study, therefore, aims to identify the trend in CSR disclosure of the tourism industry in Sri Lanka for the period from 2014 to 2018. A mixed approach of content and thematic analysis was employed in analyzing ten selected publicly quoted companies in the hotels and travels industry. The results of the study reinforce the tourism sector the pattern and the trend of CSR disclosure in heading towards effective strategic decisions. The study concludes that the growth of CSR disclosure in the hotel industry is not consistent.
Keywords: Sri lanka; Tourism industry; Corporate; Social Responsibility